FACING THE RELIGIOUS MULTICULTURALISM IN INDONESIA: MULTICULTURALISM WITH A RELIGIOUS CONTEXT - Dini Anggraheni (Universitas Aki, 2022)
This study examines how multiculturalism has been theorized, implemented, and utilized in Indonesia as a policy, discourse, and practice. The post-Suharto (the 2nd President of Indonesia) democratic process has created fresh room for formerly suppressed identities to be expressed. While much of the research on multiculturalism concentrates on racial and ethnic differences, this article attempts to widen the term's definition to encompass religious differences, as well as assess the feasibility of